BS EN 63267-2-2. Fibre optic interconnecting devices and passive components. Fibre optic connector multimode optical interfaces. Part 2-2. Connection of 50 μm core diameter multimode physically contacting fibres. Non-angled and angled for reference connector application, at wavelength of 850 nm using IEC 60793-2-10 selected A1-OM2b to A1-OM5b fibre only (8th April 2022) - British Standards Institution,
No abstract available